Aspidistra danxiashanensis (Asparagaceae), a new species from Guangdong, China - Xu, Ting; Vislobokov, Nikolay A.; Xie, Zhi Yi; Xu, Wei; Guo, Jian Qiang; Feng, Hui Zhe; Fan, Qiang (Phytotaxa, 2026)
Aspidistra danxiashanensis, a new species of Asparagaceae from Danxiashan National Nature Reserve (Guangdong, China), is described and illustrated. It resembles A. fasciaria but differs by its longer petiole, shorter lamina, urceolate perianth tube, perigone purple outside, and anthers inserted at the tube bottom. The species is known only from a single population in Danxiashan National Nature Reserve and is assessed as Critically Endangered (CR) due to its extremely restricted range and small population size.